Narrative and Linguistic Construction of Main Characters in the Film Budi Pekerti: A Semiotic Analysis of the Concept of Personality from the Islamic Perspective (Conference on English Language Teaching, 2025)
This study aims to examine the character transformation of the main character in the film Budi Pekerti (2023) through Tzvetan Todorov's structural narrative approach and the concept of personality in Islamic psychology (nafs). The study was conducted using an interpretive qualitative method based on multimodal discourse analysis, emphasizing the relationship between changes in narrative flow, visual symbolism, and the inner dynamics of the main character, Bu Prani. The results of the study show that the character's journey follows Todorov's five-stage pattern—from equilibrium to new equilibrium—which reflects the process of spiritualization of the soul from nafs ammarah to nafs muṭma'innah. The semiotic and linguistic approaches also reveal the depth of emotional expression and inner control in dealing with a reputation crisis due to cyberbullying. This study shows that film narrative can be an educational medium that represents the process of psychological healing and ethical resilience in the digital era.